Revitalisasi Pariwisata Taman Nasional Bunaken Melalui Kajian Ekoteologi Robert P. Borrong - Josua Caroles; Hendry Runtuwene (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2025)
The global ecological crisis has affected the sustainability of marine tourism in Bunaken National Park (BNP). Environmental degradation and unsustainable tourism practices indicate the absence of a strong ethical framework in managing coastal conservation areas. This study aims to analyze the revitalization of tourism in BNP through the ecotheological perspective of Robert P. Borrong.This research employs a qualitative method with a critical literature review of ecotheological writings and sustainable tourism studies. The findings indicate that Borrong’s ecotheology emphasizes ecological justice and human moral responsibility as partners of God in the care of creation. The novelty of this study lies in the formulation of a contextual ecotheological-based conceptual model for marine tourism revitalization specifically applied to Bunaken National Park. Practically, this study offers an ethical reference for churches, local communities, and park managers in promoting sustainable tourism governance.